Trisomy X and 1 29 translocation in infertile heifers - Pinheiro, L. E L [UNESP]; Almeida, I. L. [UNESP]; Garcia, J. M. [UNESP]; Basrur, P. K. (My University, 1987)
In a group of 12 Pitangueiras breed heifers exhibiting a high return rate to service, three were noted to be carriers of the 1 29 translocation. One of the heifers exhibited trisomy for the X-chromosome in addition to the 1 29 translocation. The appearance and external genitalia of the 1 29 T; trisomy X heifer were not altered, although on rectal examination the internal genitalia, including the ovaries, appeared similar to that of a prepubertal heifer. © 1987.
Keywords: 1 29 translocation; infertility; Robertsonian translocation; trisomy X; X-chromosome trisomy